Time domain thermoreflectance measurements and phonon gas modeling of the thermal conductivity of silicon doped indium phosphide pertinent to quantum cascade lasers - C. Perez; D. Talreja; J. Kirch; S. Zhang; V. Gopalan; D. Botez; B. M. Foley; B. Ramos-Alvarado; L. J. Mawst (APL Materials, 2023)
The thermal conductivity of Si-doped thin films of indium phosphide grown via metalorganic vapour-phase epitaxy at different carrier concentrations and thicknesses was measured from 80 to 450 K using time domain thermoreflectance. Additionally, phonon gas modeling was conducted to characterize the various scattering mechanisms that contribute to the thermal transport in these materials. A sensitivity analysis based on the phonon gas model showed that while thickness has a greater influence on the thermal conductivity than carrier concentration at the micron-scale for all samples, point defects due to Si-dopant atoms at carrier concentrations of ∼1019 cm−3, as well as the presence of extended defects that are most likely present due to dopant saturation, have a significant impact on thermal transport as a result of increased phonon scattering, decreasing the thermal conductivity by 40% or more.